2016
DOI: 10.1108/jgm-03-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Cultural humility and low ethnocentrism as facilitators of expatriate performance

Abstract: Purpose – For decades, expatriate scholars have understood that the individual factors of cultural humility and ethnocentrism and the contextual factors of feedback and support affect expatriates’ outcomes. The study, rooted in the observation that great advice and support are often ignored by expatriates, seeks to uncover why. Based in the humility literature, the authors test whether individual differences interact with support to affect expatriate performance. The paper aims to discuss these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 38 publications
2
35
0
1
Order By: Relevance
“…The focus has been on relations and interaction between the HQ and foreign subsidiaries and especially on the negative consequences of HQ ethnocentrism (see e.g. Caligiuri, Baytalskaya, & Lazarova, 2016; Muratbekova-Touron, 2008; Pocovnicu & Vasilache, 2012). Perlmutter’s (1969) ideas have been valuable in alerting scholars to the potential perils of ethnocentrism (if not neocolonialism) in HQ–subsidiary relations.…”
Section: From Ethnocentrism To Neocolonialism In Mnc Researchmentioning
confidence: 99%
“…The focus has been on relations and interaction between the HQ and foreign subsidiaries and especially on the negative consequences of HQ ethnocentrism (see e.g. Caligiuri, Baytalskaya, & Lazarova, 2016; Muratbekova-Touron, 2008; Pocovnicu & Vasilache, 2012). Perlmutter’s (1969) ideas have been valuable in alerting scholars to the potential perils of ethnocentrism (if not neocolonialism) in HQ–subsidiary relations.…”
Section: From Ethnocentrism To Neocolonialism In Mnc Researchmentioning
confidence: 99%
“…The function of job performance can be represented by the amount of time, energy, and effort that individuals allocate to their job and colleagues. 20 According to Caliguri, job performance is conceptualized as a multidimensional construct consisting of more than one kind of behavior. Lee et al 21 reported that in cross-cultural studies, two sub-dimensions of job performance, namely, task and contextual performance, are the most significant factors predicting the job performance of individuals during their global work experience.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation of the individual to accept an expatriate assignment and work away for home for an extended period of time is some times overlooked by organizations. An individual may want to accept the task for intrinsic reasons: such as to further their learning, and gain relevant experience; and/or for more extrinsic reasons: such as increase in salary, or a promotion, or living in a city that is seen to be more desirable for their lifestyle (Caligiuri, Baytalskaya, & Lazarova, 2016). If the task for which the individual is selected only fulfills their extrinsic desires, then the long-term job satisfaction may not be there, and can affect the individual's motivation.…”
Section: Selection Criteriamentioning
confidence: 99%